Autoproiecţie şi univers ficţional în „Istoria ieroglifică” - Simona Antofi (Revista de Istorie și Teorie Literară)
Focused on as a representative text whose semantic and structural complexity still points out its contemporary outstanding place within the critical discourse and the diachronic dynamics of the literary forms, Istoria ieroglifică depicts an authorial discourse rooted in the self-projective compensatory power of geniality as well as an allegorically encoded image of the world. From this double perspective, our study approaches the fictional mechanisms which textually generate the construction of a unique authorial image as well as of a multi-faceted complex discourse. By using the contemporary critical strategies, this type of analysis will surely redefine a text whose aesthetic value makes the Romanian literature representative within the European literary dynamics.